Mining temporal attack patterns from cyberthreat intelligence reports - Rahman, Md Rayhanur; Wroblewski, Brandon; Matthews, Quinn; Morgan, Brantley; Menzies, Timothy; Williams, Laurie (Knowledge and information systems, 2025)
Cyberthreat intelligence (CTI) reports on past cyberattacks describe the sequence of actions of attackers in terms of time. The sequence contains temporal relations among attack actions, such as a malware is first downloaded and then executed . Information related to temporal relations enables cybersecurity practitioners to investigate past cyberattack incidents and analyze attackers’ behavior. However, cybersecurity practitioners must extract such information automatically, in a structured manner, through a common vocabulary to reduce human effort and enable sharing, and collaboration. The goal of this paper is to aid security practitioners in proactive defense against attacks by automatic information extraction of temporal relations among attack actions from cyberthreat intelligence reports . We propose ChronoCTI , an automated pipeline for extracting temporal relations among attack actions from CTI reports. The attack actions are represented as MITRE ATT&CK techniques, and the relations are represented as a knowledge graph. To construct ChronoCTI , we build a ground truth dataset of temporal relations and apply large language models, natural language processing, and machine learning techniques. ChronoCTI demonstrates higher precision but lower recall performance on a real-world dataset of 94 CTI reports. We apply ChronoCTI on a set of 713 CTI reports, where we identify 9 categories of temporal attack patterns consisting of 124 temporal attack patterns. We identify that the most prevalent pattern category is to trick victim users into executing malicious code to initiate the attack, followed by bypassing the anti-malware system in the victim software systems. Based on the observed patterns, we advocate for training users about cybersecurity best practices, introducing appropriate warning messages for end-users, introducing immutable operating systems, and enforcing multi-user authentications. Moreover, we advocate that practitioners leverage the automated mining capability of ChronoCTI and design countermeasures against recurring attack patterns.